Earliest stages of visual cortical processing are not modified by attentional load - Ding, Yulong (Hum Brain Mapp, 2013)
This study investigated the effects of attentional load on neural responses to attended and irrelevant visual stimuli by recording high‐density event‐related potentials (ERPs) from the scalp in normal adult subjects. Peripheral (upper and lower visual field) and central stimuli were presented in random order at a rapid rate while subjects responded to targets among the central stimuli. Color detection and color‐orientation conjunction search tasks were used as the low‐ and high‐load tasks, respectively. Behavioral results showed significant load effects on both accuracy and reaction time for target detections. ERP results revealed no significant load effect on the initial C1 component (60–100 ms) evoked by either central‐relevant or peripheral‐irrelevant stimuli. Source analysis with dipole modeling confirmed previous reports that the C1 includes the initial evoked response in primary visual cortex. Source analyses indicated that high attentional load enhanced the early (70–140 ms) neural response to central‐relevant stimuli in ventral‐lateral extrastriate cortex, whereas load effects on peripheral‐irrelevant stimulus processing started at 110 ms and were localized to more dorsal and anterior extrastriate cortical areas. These results provide evidence that the earliest stages of visual cortical processing are not modified by attentional load and show that attentional load affects the processing of task relevant and irrelevant stimuli in different ways. Hum Brain Mapp 35:3008–3024, 2014. © 2013 Wiley Periodicals, Inc.